Responsibility of Bank Financial Institutions for The Loss of Customer Money Saved In Their Accounts - Wattimena, Yohanes Yosua; Renjaan, Henrikus; Siswani, Carina Budi (LEGAL BRIEF, 2025)
This study analyzes the legal responsibility of banking and financial institutions for the loss of customer funds stored in their accounts, a problem that has grown alongside the rapid expansion of digital banking and financial technology in Indonesia. Using a normative juridical method with statutory, conceptual, and case approaches, this research examines the legal foundations, scope of liability, and dispute-resolution mechanisms applicable when customer funds are lost due to system errors, internal negligence, or cybercrime. The findings reveal that banks’ obligations arise from multiple legal regimes: contractual liability under deposit agreements, non-contractual liability for unlawful acts, administrative obligations under the Banking Law and OJK regulations, and strict liability principles under consumer protection law. Although these norms require banks to safeguard customer assets, investigate losses, and provide compensation, practical implementation often remains weak, leaving customers in a disadvantaged position during dispute resolution. Mediation through OJK and internal complaint units provides alternative mechanisms, yet outcomes are not always binding or effective. Strengthening prudential principles, cybersecurity standards, and supervisory enforcement is essential to ensure substantive protection for customers and maintain public trust in the financial system